Calculation of Cross-Rod Spatial Structures for Seismic Impacts - Komolboy, Isabekov; Murod, Aslonov; Nizom, Ibragimov (European Journal of Life Safety and Stability (2660-9630), 2022)
The article describes a method for determining the vertical and horizontal components of the seismic load in cross-rod spatial structures with different support options and different design schemes. The distribution of seismic loads between vertical and horizontal frame elements is studied.